The collection of type specimens of the family Carabidae (Coleoptera) deposited in the Natural History Museum of Barcelona, Spain - A. Viñolas; G. Masó (Arxius de Miscel-lània Zoològica)
The type collection of the family Carabidae (Coleoptera) deposited in the Natural History Museum of Barcelona, Spain, has been organised, revised and documented. It contains 430 type specimens belonging to 155 different taxa. Of note are the large number of hypogean species, the species of Cicindelidae from Asenci Codina’s collection, and the species of Harpalinae extracted from Jacques Nègre’s collection. In this paper we provide all the available information related to these type specimens. We therefore provide the following information for each taxon, species or subspecies: the original and current taxonomic status, original citation of type materials, exact transcription of original labels, and preservation condition of specimens. Moreover, the differences between original descriptions and labels are discussed. When a taxonomic change has occurred, the references that examine those changes are included at the end of the taxa description.